2010
DOI: 10.1002/pca.1230
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a microwave‐assisted method for extracting withaferin A from Withania somnifera Dunal. using central composite design

Abstract: A pressurised MAE method for extracting WA from the plant's aerial part was optimised using factorial-based design. The net effect of time, temperature, solvent volume and its ratio suggests that the yield of WA increases until each factor reaches its optimum value, and decreases with further increase in temperature or solvent ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Conventional methods usually involve extensive drying followed by grinding into a fine powder. Next, aqueous or organic solvent‐based extraction procedures are performed where research suggests several ways in which extraction yields could be improved . For example, microwave‐assisted extraction can be optimized by modifying extraction time, temperature and solvent ratio.…”
Section: Bioactivity Of Withania Somnifera: Withaferin a And Other Wimentioning
confidence: 99%
“…Conventional methods usually involve extensive drying followed by grinding into a fine powder. Next, aqueous or organic solvent‐based extraction procedures are performed where research suggests several ways in which extraction yields could be improved . For example, microwave‐assisted extraction can be optimized by modifying extraction time, temperature and solvent ratio.…”
Section: Bioactivity Of Withania Somnifera: Withaferin a And Other Wimentioning
confidence: 99%
“…Among them, 340 papers are categorized in the subject field of chemistry. The multivariate statistical methods are most used in chromatography, spectrophotometry, electrochemistry, and applied chemistry . Our search showed that there are only eight documents in the field of experimental design published by Iranian chemists from 2000 to 2004.…”
Section: Review Of Some Published Materials By Iranian Chemists In DImentioning
confidence: 99%
“…To the best of our knowledge the quantification of SA and AVII in Atractylodes has not been reported so far. The parameters affecting UAE were optimised using central composite design (CCD; Du et al ., ; Mirzajiani et al ., ). The established method for simultaneous quantification of multicomponents in AMR proved to be a feasible method for quality control of AMR, and CCD showed ability in optimising the parameters affecting the efficiency of extracting sesquiterpenoids from AMR.…”
Section: Introductionmentioning
confidence: 97%